Letter to the Editor 32(2) - Mollah, Abid Hossain; Khan, Zohora Jameela; Begum, Most. Umme Habiba (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Abstract not available J Bangladesh Coll Phys Surg 2014; 32: 112-113